The Globalization of World Politics : An Introduction to International Relations - John Baylis (Oxford, United Kingdom Oxford University Press, 2014)
Trusted by over 300,000 students in over 120 countries, The Globalization of World Politics is the most authoritative and complete introduction to IR available, making it the go-to text for students of international relations. Now in its sixth edition, this internationally successful textbook has been fully revised and updated in light of recent developments in world politics, featuring 35 new international case studies including: the BRICs, Gaza Freedom Flotilla, Sudanese civil war, drones, Fukushima Daiichi nuclear disaster, rise of China, Occupy movement, and Syrian Revolution. A new chapter by Andrew Hurrell on rising powers and the emerging global order ensures the text continues to cover topics that will be defining the issues now and for the next generation. The unique line-up of expert contributors introduces students to the very best work within history, theory, structures, and key issues in international relations, providing a launch-pad for those who choose to progress with their IR studies. Students and lecturers are further supported by a well-resourced Online Resource Centre with the following features: Student resources: Mind maps NEW TO THIS EDITION Case studies MORE ADDED Video podcasts from the contributors NEW TO THIS EDITION Interactive library of links to journal articles, blogs and video content Flash card glossary Multiple choice questions Revision guide Instructor Resources: Case studies MORE ADDED Test bank Question bank PowerPoint slides REVISED Figures and tables from the book